SELF-ESTEEM NEGATIVELY CORRELATED WITH STRESS-RELATED EATING AMONG MEDICAL STUDENTS AFTER PANDEMIC ERA - Putri, Gyang Hanandita Gusti; Putri, Frilya Rachma; Kurnianingsih, Nia (Erudio Journal of Educational Innovation, 2023)
Pandemic of Coronaviruses Disease-19 (COVID-19) negatively influenced the mental health particularly stress and eating disorder among medical students. Previous study focused on the relationship between stress and self-esteem or eating disorders. The link between self-esteem and stress-related eating remains underexplored in the post pandemic era. This study was purposed to evaluate the relationship between self-esteem and stress-related eating among medical students after pandemic of COVID-19. This cross-sectional study involved second and third year undergraduate medical students in Universitas Brawijaya during June – July 2022. A set of self-reported questionnaires included  Rosenberg Self-Esteem Scale (RSES) and Dutch Eating Behavior Questionnaire – Emotional Eating Subscale (DEBQ-E) for measure the self-esteem and stress-related eating respectively. The form was filled in through online media. Students with previous history of eating disorders before pandemic as well as incomplete questionnaire data were excluded from study. Spearman correlation was used for statistical analysis. Ninety-two students filled in the questionnaire, only 34 students met the inclusion criteria. About 64.71% of students had low self-esteem. High stress-related eating identified in 41.18% students, particularly females. Self-esteem negatively associated with stress-related eating among participants (Spearman’s rho = -0.424; p = 0.017). Higher self-esteem decreased stress-related eating. Future studies are necessary to explore the broad range of stress sources and its impact on eating disorders among larger population.